2014
DOI: 10.1128/mbio.00911-14
|View full text |Cite
|
Sign up to set email alerts
|

O -Mannosylation in Candida albicans Enables Development of Interkingdom Biofilm Communities

Abstract: Candida albicans is a fungus that colonizes oral cavity surfaces, the gut, and the genital tract. Streptococcus gordonii is a ubiquitous oral bacterium that has been shown to form biofilm communities with C. albicans. Formation of dual-species S. gordonii-C. albicans biofilm communities involves interaction of the S. gordonii SspB protein with the Als3 protein on the hyphal filament surface of C. albicans. Mannoproteins comprise a major component of the C. albicans cell wall, and in this study we sought to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 84 publications
(134 reference statements)
2
81
0
Order By: Relevance
“…Such communities may also contain C. albicans, which is carried by~40 % of the healthy adult population (Clayton & Noble, 1966), and it is suggested that synergistic interactions between C. albicans and streptococci can promote carriage as well as disease (Dutton et al, 2014;Falsetta et al, 2014;Xu et al, 2014b). The establishment and development of such communities involves small molecule signalling between microbial components, which maximizes metabolic efficiency and controls competition of species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such communities may also contain C. albicans, which is carried by~40 % of the healthy adult population (Clayton & Noble, 1966), and it is suggested that synergistic interactions between C. albicans and streptococci can promote carriage as well as disease (Dutton et al, 2014;Falsetta et al, 2014;Xu et al, 2014b). The establishment and development of such communities involves small molecule signalling between microbial components, which maximizes metabolic efficiency and controls competition of species.…”
Section: Discussionmentioning
confidence: 99%
“…The ComCDE systems in S. gordonii, S. pneumoniae and S. mutans function as QS autoregulatory control systems, modulating gene expression patterns in different ways for the three streptococcal species (Vickerman et al, 2007;Mashburn-Warren et al, 2010;Son et al, 2012;Merritt & Qi, 2012). Since S. gordonii and C. albicans form fully integrated dual species biofilm communities (Dutton et al, 2014) we investigated the possible role of the ComCDE system in their regulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations